Inhibition of lipid peroxidation by extracts of Pleurotus ostreatus - Dissanayake, D.P.; Abeytunga, D.T.U.; Ratnasooriya, W.D.; Vasudewa, N.S. (Pharmacognosy Magazine, 2009)
Abstract: The inhibition of lipid peroxidation by Pleurotus ostreatus was established using Thiobarbituric (TBARS) assay. Three solvent extracts of P. ostreatus namely, the acetone, dichloromethane and hexane extracts were used. All three extracts showed inhibition of lipid peroxidation. The antioxidant indexes at 1.25 mg/ml concentration of acetone, dichloromethane and hexane were 38%, 43% and 36% respectively. Ergosterol was isolated and characterized from the dichloromethane extract. The antioxidant index of ergosterol at 1.25 mg/ml was 73% when tested using the same method. There exist a possibility that ergosterol can inhibit the peroxidation of common fatty acids present in egg yolk substrate (which was used for TBARS assay). The relative susceptibilities for peroxidation of ergosterol, linoleic acid and linolenic acid were investigated using computational calculations. It was found that the addition of an oxygen molecule to ergosterol is kinetically much more feasible than the addition of the same to linoleic or linolenic acids. The energy barriers for peroxidation with triplet oxygen at HF/3-21 G level of theory for ergosterol and linoleic acid (trans, trans) were 231.85 kJmol1 and 420.52 kJmol-1 respectively. It was also found that the former reaction is thermodynamically less favorable compared to the latter. The results from theoretical investigation support the experimental observation of the capability of lipid peroxidation inhibition by ergosterol.
Keywords: Antioxidant activity; basidiomycetes; energy minimization; ergosterol; Oyster mushroom; TBARS assay